1993
DOI: 10.3109/10826089309039648
|View full text |Cite
|
Sign up to set email alerts
|

Reading Ability in Patients in Substance Misuse Treatment Centers

Abstract: Adult inpatients in state-supported (public) and private substance misuse treatment settings were tested for reading ability. Patient education materials and consent forms were assessed for readability levels. Public patients' mean reading levels were significantly lower than those of private patients, and were 4 to 5 years below the level needed to read and understand standard treatment materials. More than half of the public and almost one-third of the private patients tested were reading below a 9th grade l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 6 publications
1
20
0
Order By: Relevance
“…Among clients undergoing substance misuse treatment, for example, more than half read at or below 9th grade level, often three or four grades below the reading level of most informed consent and treatment related educational materials. 2 Similar findings are demonstrated for emergency department patients, those with chronic diseases, clients of public hospitals, and those attending family planning clinics. [3][4][5][6][7][8] A recent study showed that women with low literacy skills in a low income, managed care population had less understanding of fertile periods during the menstrual cycle and indicated greater interest in learning more about birth control methods.…”
supporting
confidence: 55%
“…Among clients undergoing substance misuse treatment, for example, more than half read at or below 9th grade level, often three or four grades below the reading level of most informed consent and treatment related educational materials. 2 Similar findings are demonstrated for emergency department patients, those with chronic diseases, clients of public hospitals, and those attending family planning clinics. [3][4][5][6][7][8] A recent study showed that women with low literacy skills in a low income, managed care population had less understanding of fertile periods during the menstrual cycle and indicated greater interest in learning more about birth control methods.…”
supporting
confidence: 55%
“…McIntyre et al's [19] research emphasised the importance of health literacy as a much better predictor of health status than age, income, race, ethnicity, employment status, or educational level. However, other authors have found no relationship between variables such as age, level of education and self-reported literacy skills, and the level of health literacy [27,32].…”
Section: Health Literacymentioning
confidence: 88%
“…Poor health literacy costs the United States an estimated $100-$236 billion every year [25]. So far, in assessing health literacy in the US two kinds of instruments have been frequently used: the Test of Functional Health Literacy in Adults (TOFHLA) [26] and the Rapid Estimate of Adult Literacy in Medicine (REALM) [27].…”
Section: Health Literacymentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the available printed health information and education materials are written for reading levels of Grade 8 or higher, and thus, are not used by a large percentage of people with lower reading skills (Boyd & Citro, 1983;Doak, Doak, & Root, 1985;Meade & Byrd, 1989;Davis et al, 1993).…”
Section: Methods Participantsmentioning
confidence: 99%